A BUSCA DA INTERDISCIPLINARIDADE NAS DISCIPLINAS DE PROJETO ARQUITETÔNICO NO CURSO DE GRADUAÇÃO EM ARQUITETURA E URBANISMO - Djanine Dolovet Martins; Adriana Aparecida de Lima Terçariol (Universidade do Oeste Paulista, 2016)
The purpose of this paper is to present how the discipline of Architectural Design, specifically, the course of Architecture and Urbanism offered by that university, needs and depends on an interdisciplinary organization, involving all disciplines of the curriculum of the course grade. To develop this study, we opted for the bibliographical and documentary research as research methodology. In literature the main works were consulted: Finance (1999 1979), Morin (2007), Japiassu (1976) Luck (2001), Freire (2009). In document analysis, it was adopted as reference the Educational Project Architecture and Urbanism Course developed in Unoeste and guidelines that support the structure of undergraduate course projects in Architecture and Urbanism area. As main results, it was concluded that the discipline of Architectural Design needs this interdisciplinary approach, involving all the other disciplines of the course, as one architectural design also depends on a whole learning about different areas for its implementation.